Gestational diabetes Mellitus: integrative literature review article - Francisco A. Vieira Filho, José; Maffioletti Ferrari, Heloisa; Victor Rossoni Junior, Joamyr; Luchini Roldi, Lourdes; Antônio Souza Peichinho Filho, Marcio; Giovanna Storch Catani, Maria; Giulia Gomes Nascimento da Silva, Maria; Chiarelli Neto, Orlando (Seven Editora, 2023)
Objective: This article aims to discuss gestational diabetes mellitus (GDM), which is increasingly present during the gestational period. Elucidating about pathophysiology, epidemiology, etiology and prevention in order to spread knowledge in the academic and professional environment of the health area, amplifying the number of pregnant women diagnosed and, consequently, treated, to prevent the significant complications of this disease. Methods: In this work, an integrative literature review was carried out, using articles in the English language between the years 2010 to 2022, electronically searched in the free PubMed and UpToDate database, using the keywords: "Diabetes, Gestational", " Obesity, Maternal”, “Hypoglycemic Agents”, “Pregnancy Complications”, “Metabolic Diseases”. Results: Initially, 61 articles were identified, but 8 of these articles selected in the first instance did not meet the inclusion criteria, being excluded after analysis by the authors of this review article. In all 53 articles selected for the development of the work, they were explored in order to extract all kinds of relevant information and carry out counterpoints according to different dates and authors, resulting in a change and evolution of the methods of treatment and management of pregnant patients since 2010 up to the current scenario. Conclusion: This article made it possible to identify, through the authors’ analysis, that GDM is an underreported pathology, in which pregnant women experience the repercussions of hyperglycemia without the correct treatment. However, when the diagnosis is performed properly, therefore, therapeutic measures are easy to manage. DOI: https://doi.org/10.56238/colleinternhealthscienv1-032